From mainframes to the cloud: innovation, industrial structure, and business models in the information and communication technology industry (Revista de Administração, 2013)
Radical innovations in information technology are opening windows of opportunities for developing new business models which will affect the structure of global industry. By reviewing structural changes in the information technology industry over the past five decades, this article analyzes the relationship between innovation, the surge of paradigm firms, and business models, with the aim of contributing to the development of business strategies and public policies. The case of Google is analyzed, based on the recent literature on the information economy, in order to exemplify how technological change affects competition in the IT industry.